Edukasi Masyarakat Upaya Membangun Branding Produk UKM di Banjar Lokaserana Selama Pandemi - I Putu Aswin Anandam; Dewa Ayu Putu Adhiya Garini Putri (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The total cessation of the tourism sector in Bali during this pandemic resulted in the paralysis of the community's economy. Not a few people in Banjar Lokaserana lost their jobs and as a result some of them changed professions and tried to sell, starting from selling masks, food, to selling household furniture. However, in running their business, many people experience difficulties in promoting their products through social media, which results in limited sales reach. Branding is a business strategy to introduce the business value of a business product to consumers. Branding strategies are carried out in several aspects, such as creating a business name, logo, brand, and even promotional procedures for a product. This Non-Location KKN Report contains information about public education in efforts to build SME product branding which was carried out in the Banjar Lokaserana environment during the Covid-19 Pandemic. In the initial stage, observation methods were used to determine the target community and discuss the problems faced. In the implementation method, a work program is implemented by providing education to the target community about product branding to create attractive promotional posters using the Canva application. To find out all forms of improvement and results from the implementation of the work program, an evaluation was carried out by providing a questionnaire via Google Form media. This education aims to achieve sales results for the target community.